A Critical Study of the Wage System and Practice in Indonesia belongs to the Maqashid al-Shariah Perspective - Nur Mardhiah (Fakultas Syariah UIN Fatmawati Sukarno Bengkulu, 2022)
This study aims to analyze the wage system and practice in Indonesia from the perspective of Maqashid al-Shariah. The indicators can be seen from several applicable policies, whether they have brought benefits to the workers/laborers or not. This can be answered with an in-depth study and study seen from several aspects, including; list of decent living needs (KHL), specialization and division of labor as the basis for setting wages, wage transparency, and human resource development within companies in Indonesia. As for the methods and techniques of analysis using the content of data analysis carried out qualitatively by making interpretations of policies, rules, and empirical data obtained, then concluded as answers to research problems. Findings in the field reveal that from systems and policies, as well as practices, some companies are still unable to provide decent wages to workers/laborers or even do not meet decent living standards (KHL) in Indonesia. In addition, there are policies and regulations that come from the government or companies that are not in line due to internal factors of the company itself. This research is here to try to provide an affirmative solution by integrating the indicators of the benefit of the Maqashid al-Shariah on improving the policy and wage system in Indonesia. Penelitian ini bertujuan untuk menganalisis sistem dan praktik upah di Indonesia perspektif Maqashid al-Shariah. Adapun indikatornya dilihat dari beberapa kebijakan yang berlaku apakah sudah menghadirkan kemaslahatan bagi para pekerja/buruh atau belum. Hal tersebut dapat terjawab dengan kajian dan telaah secara mendalam dilihat dari beberapa aspek, diantaranya; daftar kebutuhan hidup layak (KHL), spesiliasi dan pembagian kerja sebagai basis dalam penetapan upah, transparansi pengupahan, serta pembinaan sumber daya manusia di lingkungan perusahaan di Indonesia. Adapun metode dan teknik analisis menggunakan konten analisis data yang dilakukan secara kualitatif dengan membuat penafsiran terhadap kebijakan, aturan, maupun data empiris yang didapatkan, kemudian disimpulkan sebagai jawaban terhadap permasalahan penelitian. Temuan di lapangan mengungkapkan, dari sistem dan kebijakan, maupun praktik beberapa perusahaan masih belum mampu memberikan upah kepada para pekerja/buruh yang layak atau/bahkan tidak memenuhi standar kebutuhan hidup layak (KHL) di Indonesia. Selain itu, kebijakan maupun aturan baik itu yang datang dari pemerintah maupun perusahaan ada yang belum sejalan dikarenakan faktor internal perusahaan itu sendiri. Penelitian ini hadir mencoba memberikan solusi afirmatif dengan mengintegrasikan indikator kemaslahatan perspektif Maqashid al-Shariah terhadap perbaikan kebijakan dan sistem pengupahan di Indonesia.